Endoscopic Brow Lift Fixation With Mitek Suture Anchors: A 9-Year Experience of a New "Ideal" Technique. Issue 2 (May 2019) - Adetayo, Oluwaseun A.; Wong, Wendy W.; Motakef, Saba; Frew, Tyler G.; Campwala, Insiyah; Gupta, Subhas C.
Purpose: In recent years, the endoscopic technique has emerged as a minimally invasive approach to forehead rejuvenation, although the specific need for and mode of brow fixation for endoscopic brow lifts remain under considerable debate. An ideal fixation device should provide non-palpable long-lasting fixation and allow retention of the device post-operatively without the need for removal. It should also allow precise intraoperative adjustment for symmetry and correction of brow ptosis. Methods: The authors describe an endoscopic brow lift technique using an absorbable bone anchor, Mitek Microfix. A retrospective chart review was conducted in patients who underwent endoscopic brow lift procedures utilizing this fixation method at an academic practice. Outcomes evaluated included operative times, reoperation rates, palpability, fixation device permanence, incremental costs comparisons to conventional methods, efficacy, and technical learning curve. Complication rates were evaluated and the economic, incremental cost analysis of current fixation methods was reviewed. Results: Eighty-two patients underwent single-procedure endoscopic brow fixation using the Mitek anchor over a 9-year period (2005-2014). The mean operative time was 100 minutes. There were no cases of implant palpability, alopecia, or other postoperative complications. Two patients underwent revision secondary lifts after an average of 5.5 months for temporal ptosis. Conclusion: The Mitek Microfix QuickAnchor provides durable, long-lasting fixation without device palpability. Its technical ease of use is demonstrated by the reasonable mean operative time achieved with the active involvement of resident surgeons. This device is operator-friendly, easy to use, fully indwelling, and provides lasting fixation without the development of palpability or alopecia.